Effects of drying process on oil quality, the bioactive properties and phytochemical characteristics of avocado (Fuerte) fruits harvested at two different maturity stages. Issue 4 (25th February 2021) - Al‐Juhaimi, Fahad; Uslu, Nurhan; Musa Özcan, Mehmet; Babiker, Elfadıl E; Ghafoor, Kashif; Mohamed Ahmed, Isam; Alsawmahi, Omer N.
Abstract: Some chemical properties, oil contents, and bioactive properties of different parts of unriped (green) and ripened "Fuerte" avocado fruits (FAF) dried in air, microwave, and oven unriped air‐dried FAF pulp showed higher (76.84%) oil contents, whereas that of microwave‐dried riped FAF pulp was 70.87%. Oil contents of FAF peel and seeds were also evaluated. Oleic, palmitic, and linoleic acids were the main fatty acids of FAF pulp and peel. The oleic acid contents of unriped and riped FAF pulps were 71.07 (oven‐dried) and 72.85% (air‐dried), respectively. The (+)‐catechin unriped and riped FAF pulp was detected to be high at 190.51 and 195.45 mg/100g in fresh samples, respectively. The results about other phenolic compounds and antioxidant activities also varied with maturity, drying method, and fruit parts. The highest 1, 2‐dihydroxybenzene were detected in ripened FAF air‐dried peel (234.74 mg/100 g) and fresh unriped FAF seed (227.18 mg/100 g), respectively. The 3, 4‐dihydroxybenzoic acid contents (102.78 mg/100 g) were determined in microwave‐dried FAF seed. Practical applications: Avocado in many countries were consumed in the form of salads with onions and cheese or soup with salt and pepper. Avocado has a high‐quality oil for the human nutrition, pharmaceutical, and cosmetics industry, and it is beneficial in human nutrition because avocado oil is rich in monounsaturated fatty acids. Avocado fruits used in the treatment of hypercholesterolemia, hypertension, type 2 diabetes mellitus, and dyslipidemia may play an important role in cardiovascular health. After harvesting, drying is one of the suitable methods for extending the shelf life of fruits or vegetables, and preventing deterioration and contamination during storage.